(3LRA ajg efJbi ef ahGFO CHj GdbGSe GdEOQjSis - (3CHh GdbGSe SYjO Hf eMeO Hf GdMSf GdGOQjSjs ((3eOjfI ZQfGWI s)
(3ChdgG (B:s
(3CNHQfG GdTjN Gdabjg GdEeGe CHh WGgQ CMeO Hf eMeO GdSdai GdCUHgGfi bGd QShd Gddg Udi Gddg Ydjg hSde (B( (3EfeG GdCYeGd HGdfjI hEfeG dCeQF eG fhi aef cGfJ gLQJg Edi Gddg hQShdg (B) s
(3BNQgG (B:s
(3hSjO GdTghQ TgQ QeVGf hSjO GdUhQ UhQI BOe Ydjg GdSdGe ced GdLRA hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG hehdGfG eMeO hBdg hUMHg hSde JSdjekG cKjQkG cKjQkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3eUOQ GbJfGA GdCUd (B:s
(3eOQjO (B(5349) s
Keywords: (3GdMOjK h GdeUWdMs